The Modelling of Wind Turbine Influcence in the Primary Radar Systems - Pidanič, Jan; Juryca, Karel; Suhartanto, Heru (University of Indonesia, 2017)
Wind turbines or wind farms present a major source of renewable energy. The expansion of wind turbines across the world rapidly increases. Unfortunately, for radar systems, wind turbines are a big source of clutter that can negatively influence the behavior of the detection capabilities of radar systems, or even totally “blind” radar systems. The problematic of mitigation of the influence of the wind turbines on radar systems is highly variable and depends on parameters of the wind turbines and radar systems. The main negative parameters of wind turbines are large Radar Cross Sections and Doppler shift spread of reflected signals. For the determination of general mitigation techniques, it is important to make a deep analysis of the different types of scenarios using a developed simulator of reflected signals from a wind turbine. This paper describes developed simulator and wind turbine parameter analysis
Modelování vlivů větrné elektrárny u primárních radarových systémů
Keywords: wind turbine; power plant; primary radar system; clutter; reflection, Radar Cross Section; větrná elektrárna; elektrárna; primární radarový systém; clutter; odrazy signálů; radar